2013
DOI: 10.1016/j.cell.2013.01.049
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Nucleoporin Nup170p in Chromatin Structure and Gene Silencing

Abstract: Embedded in the nuclear envelope, nuclear pore complexes (NPCs) not only regulate nuclear transport, but also interface with transcriptionally active euchromatin, largely silenced heterochromatin, as well as the boundaries between these regions. It is unclear what functional role NPCs play in establishing or maintaining these distinct chromatin domains. We report that the yeast NPC protein Nup170p interacts with regions of the genome containing ribosomal protein and subtelomeric genes. Here, it functions in nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
167
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(185 citation statements)
references
References 86 publications
(84 reference statements)
15
167
1
Order By: Relevance
“…Several other studies have shown an association of NPCs with silenced genomic regions and chromatin boundary. Data from yeast and Drosophila revealed heterochromatin association with stable Nups, such as Nup100 or Nup84 (Galy et al, 2000;Ruben et al, 2011;Van de Vosse et al, 2013). In human HeLa cells, ChIP analysis of Nup93 also demonstrated that Nup93 interactions include silent gene regions marked by repressive histone modifications (Brown et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have shown an association of NPCs with silenced genomic regions and chromatin boundary. Data from yeast and Drosophila revealed heterochromatin association with stable Nups, such as Nup100 or Nup84 (Galy et al, 2000;Ruben et al, 2011;Van de Vosse et al, 2013). In human HeLa cells, ChIP analysis of Nup93 also demonstrated that Nup93 interactions include silent gene regions marked by repressive histone modifications (Brown et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To test for an interaction between RSC and asymmetric nucleosomes, we analyzed the genome-wide nucleosome landscape upon partial RSC depletion ( Van de Vosse et al 2013). We observed that twofold RSC depletion resulted in an overall reduction in nucleosome occupancy at asymmetric positions ( Fig.…”
Section: Asymmetric Nucleosomes Are Sites Of Rsc Actionmentioning
confidence: 99%
“…For analysis of nucleosome positions following RSC depletion, we used published single-end nucleosome positioning data, in which the STH1 promoter was replaced by the MET3 promoter, allowing for twofold repression by a 2-h methionine treatment (Van de Vosse et al 2013; SRA accession number SRP011944). Reads from control and Sth1 depletion experiments were extended to 150 bp and smoothed with a kernel density function using a Gaussian kernel and a bandwidth of 20.…”
Section: Rsc Depletion Datamentioning
confidence: 99%
“…The dynamics of discrete chromosomal loci depend on their chromosomal and nuclear position, for which the nuclear envelope appears to play a crucial role. More specifically, the 32 chromosome ends of a haploid S. cerevisiae genome are tethered to the nuclear envelope through redundant pathways that involve Esc1, Mps3, Csm4, the silencing informatory regulator (Sir) proteins and the nuclear pore complex (NPC) (Bupp et al, 2007;Feuerbach et al, 2002;Galy et al, 2000;Hediger et al, 2002;Hiraga et al, 2008;Taddei et al, 2004;Therizols et al, 2006;Van de Vosse et al, 2013). As a result of their attachment to the nuclear envelope, subtelomere movements occur within a relatively confined environment (Heun et al, 2001;Therizols et al, 2010).…”
Section: Introductionmentioning
confidence: 99%